Critical Pedagogy and L2 Education in the Global South (2020)
ABSTRACT: Colombia, as other Latin American countries, has not been indifferent to the power of English as the language of business, international communication and academia. Since the end of the 20th century, there has been a great push in the country to promote the teaching of English: language policies have been formulated, ideal levels of proficiency have been established (based on a framework initially designed for European countries), and a national English curriculum for all grade levels has been distributed among schools. The status English has gained competes with that of other foreign languages and more evidently with heritage languages. The field of L2 education in Colombia is experiencing a tension between neoliberal interests of L2 education to support social mobility and the nation’s economic growth and political power (with a focus on linguistic and communicative competence), and alternative academic agendas grounded on the analysis of the influence of social, cultural, and economic factors on L2 teaching and learning, and on learners’ identities. In this article, I use the example of an analysis of L2 education, from a critical pedagogy standpoint, using a Latin American university as a context to depict such a contrast. This University is a place where there is confluence of diverse languages that have different social statuses: English as lingua franca, European and Asian foreign languages, and heritage languages. I argue that critical pedagogy, partly inspired in the work from intellectuals from the Hemispheric South, serves as a framework to guide analyses of power in the relationship between these languages and L1, and the effect of such relations of power on learners’ identities. Also, I contend that by using critical pedagogy in this context, it becomes transformed, nurtured, as it overlaps and dialogues with other knowledges developed in the Hemispheric South.